Design of Assessment for English Subject in Junior High School - Julianus Paken Mangewa (Jurnal Keguruan dan Ilmu Pendidikan, 2017)
The problem concerns in this study is the design assessment for English subject in junior high school. An exploratory method utilized in this study. The aim of this study is to explore or to investigate the theory of assessment design in junior high school. The design of assessment will be examined through a sequential exploratory design that employed both qualitative and quantitive data. The study will be beneficial theoretically and practically. Theoretically, the result of the study will contribute to contribute to the general understanding of curriculum-change implementation. Practically, the result will help teacher in designing English assessment more appropriately.